2020
DOI: 10.1021/acs.energyfuels.0c00174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Monomer Ratio on the Performance of Poly(octadecyl acrylate-co-styrene) as Pour-Point Depressants

Abstract: The effect of polar monomer styrene content on the effectiveness of the performance of poly­(octadecyl acrylate) (POA) pour-point depressant (PPD) was studied using the model waxy oils (MWOs) and Shengli crude oil. A set of controlled styrene content was copolymerized with octadecyl acrylate to make poly­(octadecyl acrylate-styrene) (POA-S). The performances of POA and POA-S in MWOs and Shengli crude oil were evaluated by measuring their ability to decrease pour points of model waxy oils and waxy crude oil. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Four characteristics of side chains/pendants that influence the efficacy of additives were identified, namely, functional group (Zhao et al and Wu et al), pendant length (Li et al and Deshmukh and Bharambhe , ), monomer ratio (Jiang et al, Fu et al., Yang et al), and graft density (Jiang et al). While analyzing the effects of functionality of side chains, Zhao et al studied the effect of replacing the alkyl side chain linked to the amide group in a maleic anhydride-based copolymer, with a benzene ring and a benzimidazole ring (as shown in Figure ).…”
Section: Classification Of Flow Improversmentioning
confidence: 99%
See 4 more Smart Citations
“…Four characteristics of side chains/pendants that influence the efficacy of additives were identified, namely, functional group (Zhao et al and Wu et al), pendant length (Li et al and Deshmukh and Bharambhe , ), monomer ratio (Jiang et al, Fu et al., Yang et al), and graft density (Jiang et al). While analyzing the effects of functionality of side chains, Zhao et al studied the effect of replacing the alkyl side chain linked to the amide group in a maleic anhydride-based copolymer, with a benzene ring and a benzimidazole ring (as shown in Figure ).…”
Section: Classification Of Flow Improversmentioning
confidence: 99%
“…Some authors have modified the monomer ratio and have observed the efficacies of the different polymeric additives. Jiang et al modified the alkyl amide content (octadecyl chain, nonpolar; amide, polar) in maleic anhydride-based polymers. They synthesized polymers with different amidation ratios ( f ), which indicates the number of alkyl amides resulting from maleic anhydride groups.…”
Section: Classification Of Flow Improversmentioning
confidence: 99%
See 3 more Smart Citations